2021
DOI: 10.7150/thno.54550
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-125b-5p deriving from mesenchymal stem cells promotes tubular repair by suppression of p53 in ischemic acute kidney injury

Abstract: Mesenchymal stem cells-derived exosomes (MSC-exos) have attracted great interest as a cell-free therapy for acute kidney injury (AKI). However, the in vivo biodistribution of MSC-exos in ischemic AKI has not been established. The potential of MSC-exos in promoting tubular repair and the underlying mechanisms remain largely unknown. Methods: Transmission electron microscopy, nanoparticle tracking analysis, and western blotting were used to characterize the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 55 publications
3
98
0
Order By: Relevance
“…Our previous research has confirmed the above phenomena and verified that autophagy activation could reduce SAKI (15). The role of p53 in SAKI is rarely reported, although previous studies have explored the damaging role of p53 in bilateral renal ischemia-reperfusion induced AKI and cisplatin nephrotoxic AKI (27,28). Other literature has suggested that acetylated p53 may cause damage to myocardial cells (29), liver cells (30), and neurons (31) under septic conditions by promoting apoptosis.…”
Section: Discussionsupporting
confidence: 76%
“…Our previous research has confirmed the above phenomena and verified that autophagy activation could reduce SAKI (15). The role of p53 in SAKI is rarely reported, although previous studies have explored the damaging role of p53 in bilateral renal ischemia-reperfusion induced AKI and cisplatin nephrotoxic AKI (27,28). Other literature has suggested that acetylated p53 may cause damage to myocardial cells (29), liver cells (30), and neurons (31) under septic conditions by promoting apoptosis.…”
Section: Discussionsupporting
confidence: 76%
“…MicroRNAs (miRNAs/miRs) are a novel class of non-coding small ribonucleic acids, which can regulate gene expression by suppression of mRNA translation or degradation of mRNAs ( 11 , 12 ). Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells ( 13 , 14 ). Meanwhile, miRNAs have been reported to be associated with AKI progression ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a number of exosomal proteins, miRNAs and lncRNAs have been reported to promote the progression of AKI. For example, Cao et al ( 14 ) found that exosomal miR-125b-5p deriving from mesenchymal stem cells (MSCs) could promote tubular repair by suppression of p53 in ischemic AKI; Zhang et al ( 23 ) indicated that endothelial progenitor cells-derived exosomal miR-21-5p could alleviate sepsis-induced AKI by inhibiting runt-related transcription factor 1 expression. However, the function of exosomes in AKI needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cao et al highlighted the important roles of miR-125b-5p enriched in exosomes. They found that the adhesive molecules on exosomes assisted in homing to injured areas and miR-125b-5p targeted p53 to inhibit apoptosis and promote tubular repair [ 111 ].…”
Section: Mesenchymal Stem Cell-derived Exosomes In Kidney Injury Repairmentioning
confidence: 99%